PERANCANGAN APLIKASI SEBAGAI MEDIA TANDA TERIMA TERHADAP KURIR PADA EKSPEDISI LION PARCEL BERBASIS ANDROID - Brilliant Hillary Sandy; Sitohang, Sunarsan (Computer Science and Industrial Engineering, 2025)
The development of digital technology has brought to various sectors, including the logistics and expedition industry. One of the main challenges in this industry is the manual handover process, which often poses risks. Process that is still done manually, which often leads to the risk of administrative errors, lost goods, and late deliveries.administrative errors, loss of goods, and delays in delivery. Lion Parcel, as one of the leading expedition companies in Indonesia, faces similar issues that impact the company's operational efficiency and customer satisfaction. This research aims to design an Android-based goods handover application that supports Lion Parcel's operational processes.operational process of Lion Parcel courier. This application is designed to record, track, and verify the digital handover of goods.verify the handover of goods digitally. By utilizing Android-based technologytechnology, this application can reduce manual errors, improve data accuracy, and speed up the delivery process.accuracy, and speed up the delivery process. In addition, this appalso offers additional features, such as real-time item tracking and digital signatures, which provide added value to customers withdigital signature, which provides added value to customers byincreasing transparency and trust in the service. The advantages of Android technology lie in ease of access, flexibility of development, as well as relatively affordable costs, thus enabling these applications to be widely implemented.cost, thus enabling this application to be widely deployed in the field.field. Through the implementation of this application, it is expected that operational efficiencyoperational efficiency of the company can increase, delivery time.